Transportation Problem via Median Approximation Technique for IBFS and Revised MODI’s Technique - Opara Jude; Osuagwu Chidimma Udo (Innovation in Science and Technology, 2024)
The work sought to improve the modified distribution method (MODI) and propose an approach for estimating the initial basic feasible solution (IBFS) for a transportation problem. The Median Approximation Technique (MAT), an explicit and effective approach for locating an IBFS to a transportation problem, was created and successfully tested on 10 problem sets. The created methodology, MAT, was compared to the five existing approaches for obtaining the IBFS: Vogel Approximation MethodVAM; North West Corner Method NWCM; Least Cost MethodLCM; Column Minimum MethodCMM; and Row Minimum MethodRMM in terms of iterations’ number required to reach the optimum stage. Conclusively, the MAT under development provided a better IBFS across the board, as it produced optimum solutions for around 60% of the solved problem cases, as opposed to the IBFS created by the five existing approaches employed in this study, which gave optimum solutions for roughly 0%, 20%, 20%, 10%, and 10% of the examples, respectively.